2021
DOI: 10.47059/revistageintec.v11i3.2050
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education System: Knowledge, State & Potential

Abstract: This paper embraces the study of quality parameters of higher education institutions responsible for producing employable graduates and thus resulting in enhanced industry acceptance and eventually employability. The newly introduced National Education Policy announced by the Government of India in 2020 is also being studied and discussed to detail the challenges associated with the Indian Education System, its current stature, and the scope of modifications with an intent to enhance the employability of young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…While the united states scored at the top G8 countries and 2nd globally in the 2022 GII rankings, it scored 5th among G8 countries' 2021 HDI results and was ranked 21st Globally. From a knowledge advancement perspective and investing in research and development, the USA has scored at the top globally in terms of the total number of PhDs awarded in the field of science and engineering [24], which is also aligned with the highest globally in research and development reaching three-quarters of a trillion in 2022 followed by China of half a trillion [25]. This is aligned with the outcome of recent research [26], which concluded that North America is the best performer in terms of their performance of Global Innovation.…”
Section: Usamentioning
confidence: 99%
“…While the united states scored at the top G8 countries and 2nd globally in the 2022 GII rankings, it scored 5th among G8 countries' 2021 HDI results and was ranked 21st Globally. From a knowledge advancement perspective and investing in research and development, the USA has scored at the top globally in terms of the total number of PhDs awarded in the field of science and engineering [24], which is also aligned with the highest globally in research and development reaching three-quarters of a trillion in 2022 followed by China of half a trillion [25]. This is aligned with the outcome of recent research [26], which concluded that North America is the best performer in terms of their performance of Global Innovation.…”
Section: Usamentioning
confidence: 99%